Odpowiedź :
a)
[tex]4x - 3 = 3x + 5 \\ x = 8[/tex]
b)
[tex]5x + 2 = 7 - 3x \\ 8x = 5 \\ x = \frac{5}{8} [/tex]
c)
[tex]3(x - 1) = 0 \\ 3x - 3 = 0 \\ 3x = 3 \\ x = 1[/tex]
d)
[tex] - 6(x + 1) = 24 \\ - 6x - 6 =2 4 \\ - 6x = 30 \\ x = - 5[/tex]
e)
[tex] - 7(x - 2) = 3x - 1 \\ - 7x + 14 = 3x - 1 \\ - 10x = - 15 \\ x = \frac{15}{10} = 1.5[/tex]
f)
[tex]4(x - 1) = 6(1 + x) \\ 4x - 4 = 6 + 6x \\ - 2x = 10 \\ x = - 5[/tex]
Odpowiedź:
a) 4x - 3x = 3 + 5
x = 8
b) 5x + 3x = - 2 + 7
8x = 5 |:8
x = ⁸/5
c) 3x - 3 = 0
3x = 3 + 0
3x = 3 |:3
x = 1
d) -6x - 6 = 24
-6x = 6 + 24
-6x = 30 |:(-6)
x = -5
e) -7x + 14 = 3x - 1
-7x - 3x = -14 - 1
-10x = -15 |:(-10)
x = 10/15 = ⅔
f) 4x - 4 = 6 + 6x
4x - 6x = 4 + 6
-2x = 10 |:(-2)
x = -5